THE COMPARATIVE STUDY OF USING NUMBER HEAD TOGETHER (NHT) AND COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TOWARD STUDENTS’ READING ABILITY - Cahya, Pramudita Dewi; Sholihah, Lilis (UNIVERSITAS MUHAMMADIYAH METRO ( MUHAMMADIYAH UNIVERSITY OF METRO), 2017)
Reading is one of the four language skills that has important role for the students. Every students must have good achievement in reading. That is the reason why the reading ability should be built as early as possible. The research was proposed to know the distinction between students reading ability instructed by NHT and CIRC at the ninth grade of SMPN 1 Melinting to know which one more effective between NHT and CIRC. This design is quantitative research and the researcher give pre-test and post-test to the students. The researcher used cluster random sampling with the population of the students about 117 students. From the four classes in ninth grade, the researcher took two classes as the samples. The samples are 9.1 as Experimental class and 9.2 as the control class. Based on the result of research, there is distinction between NHT and CIRC. And the last result show that NHT is more effective than CIRC toward Â reading ability in report TextÂ in SMP N 1 Melinting.